Assessment of Air Pollution Tolerance Index of Selected Plants - Nayak, Dileswar; Patel, D. P.; Thakare, H. S.; Satasiya, K.; Shrivastava, P. K. (Indian Forester, 2015)
The present study was undertaken to evaluate air pollution tolerance index (APTI) of five different plant species around industrial area and Navsari Agricultural University campus. Four physiological and biochemical parameters like relative water content, ascorbic acid content, chlorophyll content and leaf pH were used to compute the APTI values. The findings revealed that Cassia fistula showed maximum APTI value as compared to other species in the industrial area. Saraca asoca, Syzygium cumini and Cassia fistula found to be tolerant as per the APTI value in the industrial area. However, Tectona grandis and Terminalia catappa found to have intermediate sensitivity for the polluted site. Hence, it is recommended to plant Saraca asoca, Syzygium cumini and Cassia fistula trees in industrial site to cope the environmental problem. The study also suggests that performance index might be very useful in the selection of appropriate species which can be expected to perform well for the development of green environments